Identification of Coumarins and Antimicrobial Potential of Ethanolic Extracts of Dipteryx odorata and Dipteryx punctata - Bruna Cristine Martins de Sousa; Santana Pinto de Castro; Katiane Araújo Lourido; Aline Aparecida München Kasper; Geomarcos da Silva Paulino; Camila Delarmelina; Marta Cristina Teixeira Duarte; Adilson Sartoratto; Thiago Almeida Vieira; Denise Castro Lustosa; Lauro Euclides Soares Barata (Molecules, 2022)
Dipteryx odorata and Dipteryx punctata are species native to the Amazonian, traded by extractivists to obtain coumarin. We aimed to analyze the presence of coumarin in the ethanolic extracts of leaves, branches and fruits of D. odorata and D. punctata and to evaluate the antimicrobial activity of these extracts against phytopathogenic fungi and bacteria of clinical interest. Chemical analyses were performed by thin layer chromatography (TLC) and by gas chromatography coupled to mass spectrometry (GC-MS). For the antifungal assays, the fungi used were Cercospora longissima, Colletotrichum gloeosporioides, two isolates of Fusarium spp. and Sclerotium rolfsii, and the antibacterial assay was performed using the minimum inhibitory concentration (MIC) test with Burkholderia cepacia, Escherichia coli, Pseudomonas aeruginosa and Staphylococcus aureus bacteria. In D. odorata seed extracts and in D. punctata husks, endocarps, and seeds, we identified 1,2-benzopyrone. D. odorata endocarp extracts and D. punctata seeds provided the greatest decrease in mycelial growth of the evaluated phytopathogens, showing promise as an alternative control. The husk and endocarp extracts of both species had a weak effect on E. coli. This research is the first to compare the different parts of species of the genus Dipteryx and to evaluate the use of husks and endocarps of D. punctata fruits to obtain coumarin. Chemical analyses used to quantify the compounds existing in the extracts, and tests with phytopathogens in vitro and in vivo are currently being carried out.